Validating a measure of motivational regulation strategies and examining their relationship to English proficiency - Luo, Sha; Gan, Zhengdong; An, Zhujun (Studies in Second Language Learning and Teaching, 2025)
Motivational regulation has been recognized as a crucial component of self-regulated learning. This paper presents the validation of a measure of motivational regulation strategies in an English as a foreign language context (MRS-EFL). A sample of 587 college freshmen attending an English enhancement course was recruited for data collection. Confirmatory factor analysis results supported the eight-factor structure of motivational regulation strategies, indicating a strong psychometric basis. The eight-factor 30-item scale showed good validity and reliability as well as invariance across gender. The results of multivariate analysis of variance (MANOVA) further revealed discrepancies in motivational regulation strategies among students of various English proficiency levels. Our findings suggest that the MRS-EFL can serve a dual purpose, both as an evaluation instrument for educators to assess motivational regulation strategies among students and as a research tool for researchers to investigate the impact of motivational regulation strategies on English learning outcomes.